ALLERGIC CONTACT DERMATITIS AND ATOPIC DERMATITIS: HIGHLIGHTS OF THE OVERLAP SYNDROME - Liudmyla V. Konovalenko; Oleksandr I. Litus; Viktor I. Litus (Клінічна та профілактична медицина, 2024)
Introduction. The combination of atopic dermatitis (AD) with allergic contact dermatitis (ACD) or the occurrence of ACD on the background of atopic dermatitis is called the overlap syndrome. Studies have demonstrated several reasons why patients with AD have a similar or even increased risk of developing ACD compared to those without AD. Allergens and haptens are trigger factors in a group of patients with AD and ACD overlap syndrome.